Few‐Volt Operation of Printed Organic Ferroelectric Capacitor. (30th September 2015) - Noda, Yuki; Yamada, Toshikazu; Kobayashi, Kensuke; Kumai, Reiji; Horiuchi, Sachio; Kagawa, Fumitaka; Hasegawa, Tatsuo
Abstract : The fabrication of single‐crystalline thin‐film arrays for an organic ferroelectric small molecule is achieved by a simple solution process without additional thermal annealing. Based on a cooperative proton tautomerism through a hydrogen‐bonding network, films show the polarity switching with an operating voltage of less than 5 V at room temperature. This approach provides a low‐cost and eco‐friendly fabrication of ferroelectric devices.